The Semantic Cohesion between Lying and the Meanings Interprets it in Al-Zabaidi’sTaj Al-Aroos - Mustafa, Masood Sulaiman (Journal of Tikrit University for Humanities, 2022)
The theory of semantic fields is considered as a fertile domain and a place for attracting researchers since it represents one of the main domains of semantics in modern studies. It is important when the subject relates with Arabic dictionary. This is because the dictionary depends on judging the meanings by relating the meanings of the word to its family. The researcher chose Al-Murtatha’s Al-Zabidi’slexicon (Taj Al-Aroos) as a domain to study the words explaining the lies. We gave a great attention in choosing the semantic fields of the words by considering some Arabic lexicons. Our study is about the semantic cohesion between the meaning of lie which represent a contraction to honesty and the meanings which interpret the lie.